199 Autonomic function in resistant and malignant hypertension. (4th June 2021) - Alsharari, Reem; Thomas, Neil; Lip, G.; Shantsila, Alena
Abstract : Background: Enhanced sympathetic activity and reduced parasympathetic activity, assessed by heart rate variability (HRV) indices, have been linked to the pathogenesis of hypertension. Some studies showed that sympathetic and parasympathetic activity tend to restore after long-term hypertension exposure, as a result of cardiac output adaptation. It has not been known whether resistant hypertension (RH) and treated malignant hypertension (MHT) patients experienced similar restoration of autonomic balance. Purpose: To explore the autonomic changes in treated MHT, RH and normotensives subjects. Methods: We studied 23 patients with RH (57±11 y), 18 patients with treated MHT (54±13 y), and 23 normotensives controls (NC) (50±5 y). Time domain and frequency domain HRV indices of 5 minutes recordings were used to evaluate autonomic function. In the time domain, standard deviation of normal-to-normal R-R intervals (SDNN) reflect parasympathetic activity. Reduced SDNN is a marker of lower parasympathetic tone. The ratio between low frequency and high frequency spectrum was assessed in frequency domain. LF/HF increased is a marker of increased sympathetic activity. Results: The groups were matched by age and body surface area (all p>0.05). Time domain and frequency domain variables of HRV were not significantly different between three groups (p>0.05 for all) ( table 1 ) . Antihypertensive medications used were similar, except for the higher use of diuretics in RH group (100% vs. 67%, p<0.05). On linear regression, independent predictors of decreased SDNN were high creatinine level, decreased subendocardial viability ratio and increased central systolic blood pressure(p<0.05). On linear regression, independent predictor of high HF/ LF ratio was presence of left ventricular hypertrophy (β=-2.6, p=0.04). Conclusion: No differences were detected in HRV parameters between groups. These findings support the hypothesis of potential restoration of sympatho-vagal balance after prolonged hypertension exposure. Presence of target organ damage independently predicts decreased parasympathetic and increased sympathetic tone. Conflict of Interest: None